Review: the nexus of climate change, food and nutrition security and diet-related non-communicable diseases in Pacific Island Countries and Territories. (7th February 2020) - Savage, Amy; McIver, Lachlan; Schubert, Lisa
ABSTRACT: Climate change and non-communicable diseases (NCDs) are two of the most important global health challenges of this century. Pacific island countries and territories (PICTs) are particularly vulnerable to the adverse impacts of climate change and face an increasingly high burden of NCDs. This review synthesizes the evidence for the links between climate change, food and nutrition security (FNS) and NCDs in the Pacific region and outlines the possible implications of these relationships. A comprehensive search was performed on global databases including PubMed, SCOPUS and ScienceDirect, the grey literature and reference lists. Four dominant pathways between climate change, FNS and NCDs emerged from the literature: the impact of climate change on agriculture, fisheries, migration and humanitarian food assistance. These pathways, if not addressed, are likely to lead to impaired FNS and an increased burden of NCDs in PICTs. There is little doubt that Pacific nations will experience adverse impacts of climate change exacerbating existing health risks and other socio-cultural, political and economic drivers of food and nutrition insecurity and NCDs. Further research is needed to strengthen the evidence and develop integrated, context-specific solutions. It is, however, imperative to take action to address these issues via a cross-sectoral, no-regrets, health-in-all-policies approach.